A Case Report with Literature-Based Analysis of Hereditary Angioedema Caused by C1-Esterase Inhibitor Deficiency - Sufia Athar; Noureddine Korichi; Yousra Shehada Siam (Recent Developments in Medicine and Medical Research Vol. 16, 2021)
Hereditary angioedema (HAE) caused by C1-esterase inhibitor deficiency is an autosomal-dominant disease caused by a mutation in the C1-inhibitor gene. It is rare disease that is often worsened during pregnancy and childbirth. HAE, though uncommon but if untreated it may lead to maternal death. The case report presents the successful management of a 24 years patient, Gravida 2, Para 1, known case of hereditary angioedema (C1-Esterase Inhibitor Deficiency). This patient was managed with a multidisciplinary approach by an obstetrician, an immunologist, an anesthesiologist and a pediatrician. She had an uneventful antenatal period but soon after delivery developed rashes all over her body. The attack of HAE was successfully managed with fresh frozen plasma and close observation.